Bentonite reinforced Chitosan scaffold effect of bentonite exfoliation on scaffold properties - Chakraborty, Soma; Pimentel, Cristine Joy M. (2020)
Chitosan is under investigation as a biodegradable scaffolding material for tissue engineering. Crosslinked chitosan alone cannot form a self-supporting scaffold; hence, it needs reinforcement. The group reported the fabrication of chitosan scaffolds reinforced by exfoliated (E) and nonexfoliated or pristine (P) bentonite and compared their properties. Scaffolds were fabricated through the freeze-drying technique. Bentonite was exfoliated by allowing it to swell in water for a certain time interval. X-ray powder diffraction (XRD) profile showed that swelling reduced the crystallinity of bentonite. Both types of bentonite dispersed well in the chitosan matrix and imparted structural stability to the scaffolds. Scaffolds had interconnected pores; apparent porosity of scaffold with E-bentonite was higher than of scaffold with P-bentonite. The scaffolds swelled almost 35% in 3 d without losing structural integrity. The scaffolds could be compressed to 50% of their original height. The compression modulus of the scaffold with E-bentonite was higher than that of the P-bentonite scaffold.